Crystallographic characteristics of an integrally directionally solidified Nb-Ti-Si based in-situ composite. (October 2017) - Ma, Xiao; Guo, Xiping; Fu, Maosen; Guo, Haisheng
Abstract: Crystallographic characteristics have great effects on the performance of directionally solidified Nb-Ti-Si based in-situ composite, which is mainly composed of parallel Nbss/γNb5 Si3 eutectic cells along the longitudinal axis of the specimens. Nbss and γNb5 Si3 grow up in a coupled manner and exhibit preferred growth orientation along [111]Nb and 000 1 ¯ γ zone axes, respectively. Under these orientations, two types of coherent interfaces have been formed between the two phases, corresponding to the different morphologies of γNb5 Si3 . The preferred growth orientations and coherent interface structures might promote the coupled growth and enhance the stability of the eutectic cells of this in-situ composite. Graphical abstract: